The Neuroimaging Center of the Pediatric Brain Tumor Consortium–Collaborative Neuroimaging in Pediatric Brain Tumor Research: A Work in Progress - Poussaint, T. Young (AJNR Am J Neuroradiol, 2007)
SUMMARY: As an essential part of the National Cancer Institute (NCI)-funded Pediatric Brain Tumor Consortium (PBTC), the Neuroimaging Center (NIC) is dedicated to infusing the study of pediatric brain tumors with imaging “best practice” by producing a correlative research plan that 1) resonates with novel therapeutic interventions being developed by the wider PBTC, 2) ensures that every PBTC protocol incorporates an imaging “end point” among its objectives, 3) promotes the widespread implementation of standardized technical protocols for neuroimaging, and 4) facilitates a quality assurance program that complies with the highest standards for image data transfer, diagnostic image quality, and data integrity. To accomplish these specific objectives, the NIC works with the various PBTC sites (10 in all, plus NCI/ National Institute of Neurological Diseases and Stroke representation) to ensure that the overarching mission of the consortium—to better understand tumor biology and develop new therapies for central nervous system tumors in children—is furthered by creating a uniform body of imaging techniques, technical protocols, and standards. Since the inception of the NIC in 2003, this broader mandate has been largely accomplished through a series of site visits and meetings aimed at assessing prevailing neuroimaging practices against NIC-recommended protocols, techniques, and strategies for achieving superior image quality and executing the secure transfer of data to the central PBTC. These ongoing evaluations periodically examine investigations into targeted drug therapies. In the future, the NIC will concentrate its efforts on improving image analysis for MR imaging and positron-emission tomography (PET) and on developing new ligands for PET; imaging markers for radiation therapy; and novel systemic, intrathecal, and intralesional therapeutic interventions.